On unified contribution of pair Coulomb excitations in three-body reactions. Issue 14 (January 2020) - Levin, S; Budylin, A; Koptelov, Y
Synopsis: In the present work we obtain the unified contribution of pair excited states to the asymptotics (at infinity in configuration space) of the three-body absolutely continuous spectrum eigenfunctions. Note that it is the case that is most interesting and rich from the physical point of view, as it is connected in particular with re-clustering of charged quantum complexes.